MORPHOLOGICAL, PATHOGENIC AND MOLECULAR CHARACTERIZATION OF Fusarium oxysporum f.sp. ciceri ISOLATES FROM MAHARASHTRA, INDIA - Mandhare, V.K.; Deshmukh, G.P.; Patil, J.V.; Kale, A.A. (Indonesian Agency for Agricultural Research and Development - MOA, 2011)
Vascular wilt caused by Fusarium oxysporum f.sp. ciceri (FOC) is considered as one of the major factors of low productivity in chickpea. The present study was conducted to determine the morphological, pathogenic and random amplified polymorphic DNA (RAPD) variability of twenty isolates of FOC collected from the Maharashtra State of India, along with four reference isolates corresponding to four known FOC races. Pathogenicity of each isolate was confirmed using the wilt susceptible chick-pea genotype JG-62. The mycelia of all the isolates were septate, hyaline and profusely branched. All the FOC isolates produced micro- and macro-conidia in pure culture within seven days after inoculation. Based on the abilities of the isolates to cause dis-ease on an international set of chickpea differentials and genetic variability estimated by the RAPD technique, these 24 isolates were grouped into two pathotypes, i.e. pathotype I and pathotype II.